Mangroves ecosystem management strategies in Passare Apua Village, Lantari Jaya Sub-Distict, Bombana Regency, Southeast Sulawesi STRATEGI PENGELOLAAN EKOSISTEM MANGROVE DI DESA PASSARE APUA KECAMATAN LANTARI JAYA KABUPATEN BOMBANA PROVINSI SULAWESI TENGGA - Aqmal Khaery; Cecep Kusmana; Yudi Setiawan (Jurnal Silvikultur Tropika, 2016)
Mangrove ecosystem management practices that are not environmentally friendly was one of the threats made by people in coastal areas at Passare Apua Village. The study was aimed to analyze mangrove deforestation and degradation level, mangrove species composition and diversity and to formulate strategy of mangrove ecosystem management at Passare Apua Village, Southeast Sulawesi. Some analysis were done in this study such as: remote sensing system with supervised classification methods, vegetation analysis by line transect and plot methods, description and SWOT analysis. The results showed that mangrove deforestation is happened since 1981 untill 2014 as large as 1 156.81 hectares. In 1981, mangrove ecosystem in Passare Apua was dominated by non-degraded mangroves, while in 2014 dominated by severely degraded ones. Vegetation analysis results showed that there are found 13 species of mangroves. Bruguiera gymnorrhiza was a dominant species at the slightly and moderately degraded mangrove communities, while Rhizophora mucronata was a dominant species at the severely degraded mangrove community. Causative factors of mangrove degradation were economic factors, low education and skills, and lack of control from the authorities. Based on the SWOT’s diagram and matrix, the strategy position of mangrove management at the research site is located at first kuadrant (aggressive strategy).Key words: deforestation, degradation, mangrove ecosystems, mangrove management strategy, Southeast Sulawesi.